Hasil Tanaman Wortel (Daucus carota L.) di Dataran Rendah pada Berbagai Ketebalan Mulsa Jerami Padi - Ogy Farenza Ilham; Jayaputra Jayaputra; Aluh Nikmatullah; Bambang Budi Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Carrot is one of the vegetables that people like because it has many health benefits related to the content of B vitamins, vitamin C, and other substances, thereby increasing the need or demand, but not in line with the increase in the production of this plant. One of the efforts to increase production is through area expansion, and the lowlands are the target of its development. This study aims to determine the growth and yield of carrots grown in the lowlands by applying rice straw mulch. This research was conducted in a rice field area, in Bagek Polak Village, West Lombok Regency, West Nusa Tenggara with an altitude of 26 m above sea level in July-October 2020. The field experiment with the experimental method was designed according to a Randomized Block Design with one factor, namely the thickness of rice straw mulch. (m0 = no straw mulch; m1 = 1 layer mulch thickness; m2 = 2 layers mulch thickness; m3 = 3 layers mulch thickness; m4 = 4 layers mulch thickness) was repeated four times so that there were 20 experimental units. The results showed that rice straw mulch had a significant effect on the growth and yield of carrots in the lowlands. The use of 4 layers of rice straw mulch was could increase the growth and yield of carrots by 2647.75 gr/m2 or the equivalent of 21,182 tons/ha. layer; expansion; production; vegetables; tubers